1991
DOI: 10.1111/j.1365-3040.1991.tb01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll and light gradients in sun and shade leaves of Spinacia oleracea

Abstract: Abstract. Light gradients were measured and correlated with chlorophyll concentration and anatomy of leaves in spinach (Spinacia oleracea L.). Light gradients were measured at 450, 550 and 680 nm within thin (455 μm) and thick (630 μm) leaves of spinach grown under sun and shade conditions. The light gradients were relatively steep in both types of leaves and 90% of the light at 450 and 680 nm was absorbed by the initial 140 μm of the palisade. In general, blue light was depleted faster than red light which, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
150
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(172 citation statements)
references
References 25 publications
16
150
0
6
Order By: Relevance
“…In spinach there is qualitative agreement between the depth of penetration of light, measured with a fibre-optic probe (Cui et al 1991), and corresponding chlorophyll fluorescence profiles (Fig. 12).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In spinach there is qualitative agreement between the depth of penetration of light, measured with a fibre-optic probe (Cui et al 1991), and corresponding chlorophyll fluorescence profiles (Fig. 12).…”
Section: Discussionmentioning
confidence: 58%
“…Despite leaf anatomical adaptations such as palisade tissue that facilitate the penetration of light (Vogelmann & Martin 1993), light gradients within leaves are relatively steep (Vogelmann, Bornman & Josserand 1989;Cui, Vogelmann & Smith 1991) implying that there may be relatively steep gradients in absorbed quanta within the mesophyll. This would lead to departure from the ideal situation where there are minimal gradients in light and CO 2 .…”
mentioning
confidence: 99%
“…Leaves grown in direct sunlight are usually smaller and thicker with closer vein spacing compared to shaded leaves that are larger and thinner with more widely separated veins (e.g., Wylie 1949, 1951, Esau 1977, Cui et al 1991, Ashton & Berlyn 1994, Yano & Terashima 2004, Terashima et al 2006. Epidermal layers, especially the adaxial epidermis, are thicker in sun leaves than in shade leaves.…”
Section: Introductionmentioning
confidence: 99%
“…In order to examine relationships between leaf structure and whole-leaf photosynthetic performance, it is necessary to be able to measure light, CO # and photosynthesis at the tissue level. Using microscopic light sensors inserted into leaves, it has been shown that light declines rapidly and exponentially within the leaf (Vogelmann et al, 1989 ;Cui et al, 1991 ;Vogelmann & Martin, 1993 ;Vogelmann et al, 1996). In spinach, light within the blue and red parts of the spectrum is absorbed almost completely by the initial palisade cell layers and it is primarily green light that remains for photosynthesis in tissues located deeper within the leaf (Cui et al, 1991 ;Sun et al, 1998).…”
Section: mentioning
confidence: 99%
“…Using microscopic light sensors inserted into leaves, it has been shown that light declines rapidly and exponentially within the leaf (Vogelmann et al, 1989 ;Cui et al, 1991 ;Vogelmann & Martin, 1993 ;Vogelmann et al, 1996). In spinach, light within the blue and red parts of the spectrum is absorbed almost completely by the initial palisade cell layers and it is primarily green light that remains for photosynthesis in tissues located deeper within the leaf (Cui et al, 1991 ;Sun et al, 1998). Correspondingly, the distribution of absorbed quanta across the mesophyll tissues is very steep, implying that there could be steep gradients in photosynthetic performance within the leaf (Evans, 1995).…”
Section: mentioning
confidence: 99%